REGULASI PENANGGULANGAN BENCANA DI KABUPATEN KEDIRI - Isbandono, Prasetyo; Prastyawan, Agus (JPSI (Journal of Public Sector Innovations), 2018)
Geographically Indonesia is a meeting of four tectonic plates, namely the Asian Continent, the Australian Continent, the Indian Ocean and the Pacific Ocean. The South and East parts have volcanic arc extending from Sumatra-Java Island-Nusa Tenggara-Sulawesi, in the form of volcanic mountains. These conditions?are potentially at the same time prone to disasters such as volcanic eruptions, earthquakes, tsunamis, floods and landslides. Data shows that Indonesia is one of the countries with high risk of earthquakes in the world, more than 10 times the risk of earthquakes in the United States (Arnold, 2014). According to the Chief?Executive of the East Java Regional Disaster Management Agency there are various disaster risks from earthquakes, tsunamis, landslides, floods, droughts, tornadoes, fires, volcanic eruptions (Sudarmawan, 2014). For this reason, it is necessary to improve disaster management, both regulations that are the legal basis and management of disaster management institutions in a more professional manner.